2022
DOI: 10.1099/mic.0.001148
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel gene required for competitive growth at high temperature in the thermotolerant yeast Kluyveromyces marxianus

Abstract: It is important to understand the basis of thermotolerance in yeasts to broaden their application in industrial biotechnology. The capacity to run bioprocesses at temperatures above 40 °C is of great interest but this is beyond the growth range of most of the commonly used yeast species. In contrast, some industrial yeasts such as Kluyveromyces marxianus can grow at temperatures of 45 °C or higher. Such species are valuable for direct use in industrial biotechnology and as a vehicle to study the genetic and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In a recent comparative omics study, we discovered that genes that were evolutionarily young and / or unique to K. marxianus are overrepresented among genes that display differential expression when growing under stressful conditions (Doughty et al , 2020). We also established that at least one of these genes is required for competitive growth at high temperature (Montini et al , 2022). These findings reinforce the need to thoroughly explore and characterise the K. marxianus genome as many of the unique phenotypic traits in K. marxianus could be due to genes not yet characterised in any species, or indeed to known genes that are regulated differently or encode proteins with alternative functionality.…”
Section: Introductionmentioning
confidence: 96%
“…In a recent comparative omics study, we discovered that genes that were evolutionarily young and / or unique to K. marxianus are overrepresented among genes that display differential expression when growing under stressful conditions (Doughty et al , 2020). We also established that at least one of these genes is required for competitive growth at high temperature (Montini et al , 2022). These findings reinforce the need to thoroughly explore and characterise the K. marxianus genome as many of the unique phenotypic traits in K. marxianus could be due to genes not yet characterised in any species, or indeed to known genes that are regulated differently or encode proteins with alternative functionality.…”
Section: Introductionmentioning
confidence: 96%
“…No conserved thermotolerance mechanism has been found in thermotolerant yeasts [ 78 ]. It has been reported that an evolutionary young gene with an unknown function was required for the competitive growth of K. marxianus at a high temperature [ 79 ]. However, this gene did not confer thermotolerance to Kluyveromyces lactis , indicating that thermotolerance might be linked to the de novo emergence of species-specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…If adaptive traits in K. marxianus were mediated by hundreds of independent variants, it would conform to the current view of dizzying genetic complexity as the rule rather than the exception for trait variation, across the tree of life 56,57 . In fact, even our large set of loci with signatures of selection could represent an underestimate of the full genetic architecture of K. marxianus traits, given the potential of false negatives in our approach as well as the contribution from species-specific genes 58 not analyzed here. But even as they stand, the derived alleles we have discovered in K. marxianus represent candidate determinants that would be sufficient to reconstitute K. marxianus traits in a stress-sensitive background; as such, they provide an important complement to the few reports focused on genes necessary for thermotolerance in this species 10,13,58 .…”
Section: Discussionmentioning
confidence: 99%